2015
DOI: 10.3389/fendo.2015.00175
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Hypoglycemia Increases Anxiety and Amygdala Norepinephrine Release During Subsequent Hypoglycemia

Abstract: Recurrent hypoglycemia (RH) is a common and debilitating side effect of therapy in patients with both type 1 and, increasingly, type 2 diabetes. Previous studies in rats have shown marked effects of RH on subsequent hippocampal behavioral, metabolic, and synaptic processes. In addition to impaired memory, patients experiencing RH report alterations in cognitive processes that include mood and anxiety, suggesting that RH may also affect amygdala function. We tested the impact of RH on amygdala function using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In this study, by subjecting adolescent rats to a typical Western-type obesogenic diet, we were able to reproduce various metabolic phenotypes associated with obesity. For instance, we observed postprandial hypoglycemia in the animals fed the WD, a condition commonly associated with anxiety and emotionality in both humans (Strachan et al, 2000) and rats (McNay, 2015). Not surprisingly, we report increased leptin levels in the rats that consumed the WD, and a robust correlation between TG and leptin.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, by subjecting adolescent rats to a typical Western-type obesogenic diet, we were able to reproduce various metabolic phenotypes associated with obesity. For instance, we observed postprandial hypoglycemia in the animals fed the WD, a condition commonly associated with anxiety and emotionality in both humans (Strachan et al, 2000) and rats (McNay, 2015). Not surprisingly, we report increased leptin levels in the rats that consumed the WD, and a robust correlation between TG and leptin.…”
Section: Discussionmentioning
confidence: 96%
“…Previous animal studies examining spatial working memory and hippocampal function reported that RH enhances spatial working memory in rats in euglycemia but impairs it during subsequent hypoglycemic episodes . Reports also demonstrate increased anxiety in previously RH‐exposed rats during acute hypoglycemia and decreased mental flexibility when euglycemic . Furthermore, the hippocampal synaptic function was found to be markedly impaired in RH‐exposed rats during further hypoglycemic conditions .…”
Section: Introductionmentioning
confidence: 91%
“…Exposure of ITD rats to RH-RH was induced 2-3 weeks after insulin pellet implantation, with the aim of maintaining blood glucose levels in the moderate hypoglycemia range for 3 hours, by s.c. injection of Novolog (insulin aspart, Novo Nordisk, AIS, Denmark) (Dave, et al, 2011). Duration, frequency and total number of hypoglycemia episodes was decided based on earlier studies (McNay et al, 2006;Herzog et al, 2008;Won, et al, 2012;McNay, 2015). Glucose levels were measured at baseline and every hour during hypoglycemia.…”
Section: Induction Of Diabetes-malementioning
confidence: 99%